Pemodelan Kontroler-Otomatik dengan Intervensi pada Pengendali Temperatur Tanah dan Kelembaban - Simamora, S N M P (Universitas Mandiri Bina Prestasi, 2024)
Soil fertility is influenced by two dominant parameters, namely soil temperature and humidity. If one exceeds the reference value, it will certainly affect the level and level of soil fertility. Although nutrient management is also important, temperature and humidity parameters are the two main factors that must be considered so that ideal fertility levels can be maintained. It is necessary to have an instrument to control and to stabilize so that the soil temperature and humidity values can always be maintained; citing the need to avoid biased decisions if they are not based on empirical values. In this research, a series of tests have been carried out using an automatic controller, namely an instrument built and designed to have the capability to control soil temperature and humidity. The use of a specific sensor can detect changes in sensitivity in the soil, for temperature and humidity parameters. The test results show that in a series of trials using ten test scenarios; it was found that every environmental condition that is changed by direct intervention on the sensor shows that the automatic controller can quickly and in real-time provide feedback in the form of visuals and sounds as a warning that there has been a significant environmental change, so that action must be taken to return the soil condition to its normal reference-value.